The Dynamic of Contextualization in Indonesian Qur'anic Tafsirs: A Comparative Study of Tafsir Al-Azhar and Tafsir Al-Mishbāh on The Story of The Prophet Moses - Mujahidin, Anwar; Itmam, Muhammad Shohibul; Rofiq, Ahmad Choirul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
The Indonesian Qur’anic tafsirs represent a contextual approach. Each tafsir scholar has different characteristics in contextualizing the meaning of the Qur’an so that it is relevant to contemporary Indonesian society. This article aims to show the dynamic character of Indonesian Qur’anic interpretation in contextualizing the meaning of the verses about Moses in the Indonesian context. This research uses a comparative method against the al-Azhar tafsir written by Haji Abdul Malik bin Karim Amrullah, also known as Hamka, and the Tafsir al-Mishbāh by M. Quraish Shihab. The three aspects compared and the research questions include: How is the story of Prophet Moses narrated in the two tafsir books? What are the interpretation methods used in the verses about the story of Prophet Moses, and how can the lessons from the story of Prophet Moses align with the Indonesian cultural context? The research results show that both tafsir books have similarities in making the story of Moses relevant to Indonesian society. The difference is that Tafsir al-Mishbāh appears more disciplined in following the textual meaning of the Qur’anic verses. In contrast, Tafsir al-Azhar is more flexible in its storytelling improvisation, making the story of Moses more cohesive and engaging. Shihab understands the story of Moses as Allah’s plan to overthrow human arrogance (Pharaoh), with a narrative flow following Allah’s laws. This retelling represents Shihab’s traditionalist and pragmatic thinking. In contrast, Hamka is more rational and critical. He views the story of Moses as a struggle and heroism that teaches the importance of hard work and intelligence in facing life’s challenges. The findings of this research contribute to showing the dynamic nature of Indonesian contextual tafsir. It illustrates how the Qur’anic interpretation maintains its textual meaning while remaining relevant for contemporary readers.